Dampak keberadaan PT Socfindo Lae Butar terhadap Masyarakat di Desa Rimo dan Desa Lae Butar Kabupaten Aceh Singkil - Agusra Agusra; Ruaida Ruaida; Zulfadli Zulfadli (Jurnal Serambi Ekonomi dan Bisnis, 2018)
This research aim to find out the impact of the existence of PT Socfindo Lae Butar to the community in Rimo Village and Lae Butar Village. Specifically, this study aims to find out: (1) public response regarding the existence of PT Socfindo Lae Butar and (2) to see the positive impact and negative impact of PT Socfindo Lae Butar existence. This research uses qualitative approach in the form of descriptive. This research data comes from people who have been determined by the author, with criteria representing government apparatus, public figures, employees of PT Socfindo Lae Butar and Rimo Village community and Lae Butar Village. While the data collection is done by interview and observation. Based on the results of data analysis findings of this study can be put forward as follows. First, the public response to the existence of PT Socfindo Lae Butar is seen from the negative aspect, (1) the community considers that the existence of PT Socfindo Lae Butar still has not benefited the local people especially Rimo Village and Lae Butar Village. (2) the company's environment still has a negative impact, especially from air pollution either from the smell of waste or from the smoke of the factory. (3) noise. (4) the existence of companies that are not strategic. (5) lack of employment especially for Rimo villagers and Lae Butar Village. (6) the company's CSR implementation to society is not yet clear. Second, public response to the existence of PT Socfindo Lae Butar seen from the positive aspects. (1) the public can open a business in the company environment. (2) expanding employment. (3) can reduce unemployment. (4) improving economic outcomes of the population. (5) the existence of corporate CSR, but needs to be improved again. The conclusion of this research is, that the existence of PT Socfindo Lae Butar greater negative influence compared with positive influence.